Analysis of the influence of the angular position of the cleat in kinematics and kinetics - Sola-Lopez, J.; Castillo-López, J. M.; Panera-Rico, E.; Reina-Bueno, M.; Fernández-Seguín, L. M.; Ramos-Ortega, J. (Applied Sciences, 2023)
Objective: The aims that we set in this study were to analyse the kinematic and kinetic changes in the lower limbs of cyclists when using the utility model, nº of publication ES 1078023, which consists of a system of cleats with an exact omnidirectional adjustment and without oscillations between the shoe and the pedal. Methods: This is a quasi-experimental, longitudinal and prospective study with a non-randomized sampling. The sample was made up of 34 cyclists. The variables studies focused on the kinematics of each joint of the lower limb in three planes and the kinetics in the function of the angular position of the cleat. They had the Bioval® system put in place, through which the kinematic parameters were recorded at the points marked on the lower limb for 20 s. Three systems were used for the kinetics (Power Tap, Rotor and Pioneer), recording the power developed for 1 min for each of the study situations. Results: Regarding the kinematic variables, statistically significant differences were found for the three planes in all of the structures studied. As for the kinetics, statistically significant differences were also observed, both when analyzing them globally and when doing so for each of the systems. Conclusions: The variation in the rotational position of the cleat influences both the cyclist`s kinematics and dynamics.